Enhanced target-specific delivery of docetaxel-loaded nanoparticles using engineered T cell receptors. Issue 35 (25th August 2021) - McDaid, William J.; Lissin, Nikolai; Pollheimer, Ellen; Greene, Michelle; Leach, Adam; Smyth, Peter; Bossi, Giovanna; Longley, Daniel; Cole, David K.; Scott, Christopher J.
Abstract : High-affinity TCRs offer the potential to target chemotherapeutic drug-loaded nanoparticles specifically to tumour cells expressing tumour-specific peptides minimising off-target effects. Abstract : For effective targeted therapy of cancer with chemotherapy-loaded nanoparticles (NPs), antigens that are selective for cancer cells should be targeted to minimise off-tumour toxicity. Human leukocyte antigens (HLAs) are attractive cancer targets as they can present peptides from tumour-selective proteins on the cell surface, which can be recognised by T cells via T cell receptors (TCRs). In this study, docetaxel-loaded polymeric NPs were conjugated to recombinant affinity-enhanced TCRs to target breast cancer cells presenting a tumour-selective peptide-HLA complex. The TCR-conjugated nanoparticles enabled enhanced delivery of docetaxel and induced cell death through tumour-specific peptide-HLA targeting. These in vitro data demonstrate the potential of targeting tumour-restricted peptide-HLA epitopes using high affinity TCR-conjugated nanoparticles, representing a novel treatment strategy to deliver therapeutic drugs specifically to cancer cells.